Improvement of Mechanical and Rheological Properties of Natural Rubber for Anti-Vibration Applications - Abd Ali, Nabel k.; Farhan, Malia. M.; . Moosa, Abbas S (Al-Khwarizmi Engineering Journal, 2017)
Abstract This research aims to study and improve the passivating specifications of rubber resistant to vibration. In this paper, seven different rubber recipes were prepared based on mixtures of natural rubber(NR) as an essential part in addition to the synthetic rubber (IIR, BRcis, SBR, CR)with different rates. Mechanical tests such as tensile strength, hardness, friction, resistance to compression, fatigue and creep testing in addition to the rheological test were performed. Furthermore, scanning electron microscopy (SEM)test was used to examine the structure morphology of rubber. After studying and analyzing the results, we found that, recipe containing (BRcis) of 40% from the natural rubber has the best mechanical and physical specifications to be used in applications that require the presence of rubber, resistant to vibration. Keywords: Ant vibration behavior , Natural rubber, Synthetic rubber, master batch.